Circulating Sclerostin and Irisin Are Related and Interact with Gender to Influence Adiposity in Adults with Prediabetes - Theerawut Klangjareonchai; Hataikarn Nimitphong; Sunee Saetung; Nuttapimon Bhirommuang; Rattanapan Samittarucksa; Suwannee Chanprasertyothin; Rattana Sudatip; Boonsong Ongphiphadhanakul (International Journal of Endocrinology)
Objectives. Sclerostin, an osteocyte-specific protein, has been found to be related to adiposity and glucose metabolism. Irisin, a myokine, can affect browning of white fat and influence glucose and energy homeostasis. Taken together, this suggests a probable network among fat, bone, and muscle that may influence health outcomes. The aims of this study were to investigate the relationship of circulating sclerostin and irisin and their association with adiposity (assessed by body mass index (BMI)). Materials/Methods. A cross-sectional study included 98 adults with impaired fasting glucose and/or impaired glucose tolerance. 75 gm OGTT was performed in all subjects. Fasting plasma samples were obtained for glycated hemoglobin, calcium, creatinine, serum sclerostin and irisin. Results. Circulating irisin and sclerostin were highly correlated (r=-0.4;P<0.001). After controlling for age, gender, and BMI, irisin was significantly related to sclerostin (P<0.001). Multivariate linear regression analysis demonstrated that circulating sclerostin (β=-0.45;P<0.05) and irisin (β=-0.46;P<0.05) were negatively associated with BMI, independent of age in males. In females, no relationship of sclerostin or irisin to BMI was found. Conclusions. Circulating irisin and sclerostin are highly related. Interventions targeting irisin could affect sclerostin and vice versa.